62.0k views
5 votes
There is one point of intersection in the graphs of the conics

There is one point of intersection in the graphs of the conics-example-1

1 Answer

0 votes

We are given the following system of equations:


\begin{gathered} (x+1)^2+(y+2)^2=16,\text{ (1)} \\ (y+2)^2=4(x-3),\text{ (2)} \end{gathered}

We are asked to find the point of interception or equivalently find the solution to the system. To do that, we will replace the value of (y+2) from equation (2) into equation (1), like this:


(x+1)^2+4(x-3)=16

Now we will solve the parenthesis. For the parenthesis on the left we'll use the following property:


(a+b)^2=a^2+2ab+b^2^{}_{}

Solving we get:


x^2+2x+1+4x-12=16

Adding like terms:


x^2+6x-11=16

Now we will subtract 16 on both sides:


\begin{gathered} x^2+6x-11-16=0 \\ x^2+6x-27=0 \end{gathered}

Now we will solve this equation using the quadratic formula, that is:


x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}

Where:


\begin{gathered} a=1 \\ b=6 \\ c=-27 \end{gathered}

Replacing we get:


x=\frac{-6\pm\sqrt[]{6^2-4(1)(-27)}}{2(1)}

Now we solve the operations:


x=\frac{-6\pm\sqrt[]{144}}{2}
x=(-6\pm12)/(2)
x_1=(-6+12)/(2)=3
x_2=(-6-12)/(2)=-9

Now we replace the values of "x" in equation (2)


(y+2)^2=4(x-3)

For x = 3


\begin{gathered} (y+2)^2=4(3-3) \\ (y+2)^2=0 \end{gathered}

Now we solve for "y", by taking square roots on both sides:


\begin{gathered} (y+2)=0 \\ y=-2 \end{gathered}

For x = -9


\begin{gathered} (y+2)^2=4(-9-3) \\ (y+2)^2=4(-12) \end{gathered}

Taking square root:


\begin{gathered} (y+2)=\sqrt[]{4(-12)} \\ (y+2)=\sqrt[]{-48\text{ }} \end{gathered}

Since we get the square root of a negative number there are no real "y" solution for x = -9, therefore, the only real solution is (x,y)=(3,-2)

User Despina Kastani
by
4.9k points